The effects of adding Leucine to pre and postexercise carbohydrate beverages on acute muscle recovery from resistance training - Stock, M. S.; Young, J. C.; Golding, L. A.; Kruskall, L. J.; Tandy, R. D.; Conway-Klaassen, J. M.; Beck, T. W. (The Journal of Strength and Conditioning Research, 2010)
The present study examined the effects of adding leucine to pre and postexercise carbohydrate beverages on selected markers of muscle damage, delayed-onset muscle soreness (DOMS), and squat performance for up to 72 hours after lower-body resistance training. Seventeen resistance trained men (mean ± SD age 22.9 ± 2.9 years) and 3 resistance trained women (mean ± SD age 21.6 ± 2.6 years) performed 6 sets of squats to fatigue using 75% of the 1 repetition maximum. Each subject consumed a carbohydrate beverage 30 minutes before and immediately after exercise with or without the addition of 22.5 mg/kg (45 mg/kg total) of leucine in a randomized, double-blind fashion. Serum creatine kinase (CK), lactate dehydrogenase (LDH), and DOMS were analyzed immediately before (TIME1), 24 (TIME2), 48 (TIME3), and 72 (TIME4) hours after exercise. The subjects repeated the squat protocol at TIME4 to test recovery. No differences were observed between groups for squat performance, defined as the total number of repetitions performed during 6 sets of squats, for both TIME1 and TIME4. The addition of leucine did not significantly decrease CK and LDH activity or DOMS. These results suggested that adding leucine to carbohydrate beverages did not affect acute muscle recovery and squat performance during both initial testing and during a subsequent exercise bout 72 hours later in resistance trained subjects.